2015
DOI: 10.1136/vr.103093
|View full text |Cite
|
Sign up to set email alerts
|

Best in show but not best shape: a photographic assessment of show dog body condition

Abstract: Previous studies suggest that owners often wrongly perceive overweight dogs to be in normal condition. The body shape of dogs attending shows might influence owners' perceptions, with online images of overweight show winners having a negative effect. This was an observational in silico study of canine body condition. 14 obese-prone breeds and 14 matched non-obese-probe breeds were first selected, and one operator then used an online search engine to identify 40 images, per breed, of dogs that had appeared at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
1
8
2
Order By: Relevance
“…This result is in line with studies investigating breed differences in obesity (e.g. [ 20 , 21 ]). The hound and gun dog group (such as Labrador retrievers and Basset hounds) were those that were most prone to obesity; meanwhile, working breeds (such as the Doberman) were usually normal weight.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result is in line with studies investigating breed differences in obesity (e.g. [ 20 , 21 ]). The hound and gun dog group (such as Labrador retrievers and Basset hounds) were those that were most prone to obesity; meanwhile, working breeds (such as the Doberman) were usually normal weight.…”
Section: Introductionsupporting
confidence: 91%
“…at an ambiguous position). Based on the differences in obesity proneness among dog breeds [ 13 , 20 , 21 ], we expected that overweight and obesity-prone dogs would show higher/non-selective food responsiveness, so they will approach the ambiguous location faster than the normal weight and non-obesity-prone dogs (i.e. they will show ‘positive expectancy').…”
Section: Introductionmentioning
confidence: 99%
“…The best-performing dogs are awarded and can also receive higher show awards (certificates) in the dog shows, and may thus set the standard for other dogs of the same breed, or dog show merits may be used in selection of parent animals. A few studies have assessed body condition score (BCS) in show dogs and have found that 20-60% of participating dogs may be overweight [27][28][29]. To our knowledge, no previous investigation has been performed on BCS in Swedish show dogs, so the prevalence of overweight or obese dogs among Swedish show dog populations is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The excessive food intake and/or inadequate energy use are among the main causes of obesity in dogs [16]. In addition, some breeds of dogs are more predisposed to weight gain, such as labrador retriever, golden retriever and pug [3,7,25].…”
Section: Introductionmentioning
confidence: 99%